Ways to increase efficiency of aggregates on gas pumping gas trunk pipelines - A. A. Dzino; A. N. Noskov; O. S. Malinina (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
When transporting produced natural gas with the help of gas-pumping units, a large amount of lowtemperature heat is generated. When calculating the direct thermodynamic cycle, water and alternative working substances are considered. For the more efficient use of waste heat in the forward cycle, instead of a blade turbine, the use of a screw expander with dry saturated steam at the inlet is proposed. Results are obtained on the calculation of the compressor station and gas turbine plant, on the basis of which the most preferred working substance for the forward cycle is chosen